Extracellular vesicle mimetics as delivery vehicles for oligonucleotide-based therapeutics and plasmid DNA - Oshchepkova, Anastasiya; Chernikov, Ivan; Miroshnichenko, Svetlana; Patutina, Olga; Markov, Oleg; Savin, Innokenty; Staroseletz, Yaroslav; Meschaninova, Mariya; Puchkov, Pavel; Zhukov, Sergey; Kupryushkin, Maxim; Maslov, Mikhail; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Small membrane particles called extracellular vesicles (EVs) transport biologically active cargo between cells, providing intercellular communication. The clinical application of EVs is limited due to the lack of scalable and cost-effective approaches for their production and purification, as well as effective loading strategies. Here we used EV mimetics produced by cell treatment with the actindestabilizing agent cytochalasin B as an alternative to EVs. Cytochalasin-B-inducible nanovesicles (CINVs) demonstrated unique properties for the delivery of therapeutic nucleic acids. CINVs delivered a fully modified N-(methanesulfonyl)-or mesyl (µ-) antisense oligonucleotide to B16 melanoma cells, selectively decreasing the level of target microRNA-21 with effectiveness comparable to that observed upon Lipofectamine 2000-mediated delivery. The efficiency of the CINV-mediated delivery of plasmid DNA encoding EGFP varied depending on the type of recipient cells. Surprisingly, under experimental conditions, CINVs were unable to deliver both modified and natural short RNA duplexes-small interfering RNA and immunostimulatory RNA-probably due to their poor loading into CINVs.